Quasi self-dual codes over non-unital rings of order six - Alahmadi,Adel (Universidad Católica del Norte, Departamento de Matemáticas, 2020)
Abstract: There exist two semi-local rings of order 6 without identity for the multiplication. We classify up to coordinate permutation self-orthogonal codes of length n and size 6 n/2 over these rings (called here quasi self-dual codes or QSD) till the length n = 8. To any such code is attached canonically a ℤ 6 -code, which, when self-dual, produces an unimodular lattice by Construction A.